2016
DOI: 10.5935/0103-5053.20160073
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Profile and Cytotoxic Activity of Leaf Extracts fromSennaspp. from Northeast of Brazil

Abstract: Methanolic, diethyl ether and n-hexane extracts of leaves of four species of Senna (S. gardneri, S. macranthera, S. splendida and S. trachypus) were analyzed by gas chromatography coupled to mass spectrometry (GC-MS). Using linear retention indices and mass spectral data, 34 compounds were identified, including fatty acids, flavonoids, terpenoids and steroids that were not reported previously for these species. Additionally, the cytotoxicity of the extracts against different tumor cell lines was determined. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…After, was added MSTFA (200 μL), and water bath at 37 °C for 30 min. 23 The extracts were then filtered and stored for 24 h at 4 °C prior to chromatographic analysis.…”
Section: Extraction and Derivatizationmentioning
confidence: 99%
“…After, was added MSTFA (200 μL), and water bath at 37 °C for 30 min. 23 The extracts were then filtered and stored for 24 h at 4 °C prior to chromatographic analysis.…”
Section: Extraction and Derivatizationmentioning
confidence: 99%
“…The phytochemical investigations on Astragalus creticus lead to the isolation of a tannin, one fatty acid, one terpene, four flavonoids and two sterols. The purified compounds were reported previously from various plants like Ethyl gallate from Acacia leucophloea and Rhynchosia phaseoloides (Calderon et al 2006;Leela and Saraswathy 2013), 1-Triacontanoic acid from Desmodium sambuense and Senna trachypus (Li et al 2010;Silva et al 2016), Kaemferol-7-O--Dglucopyranoside from Cassia renigera and Securigera securidaca (Behbahani et al 2014;Singh et al 2011) of family Fabaceae. The rest of the compounds were already Antimicrobial resistance is increasing day by day (Mayers et al 2017).…”
Section: Discussionmentioning
confidence: 91%
“…A previous study has identified neophytadiene in cytotoxic fractions of Senna spp. (Leguminosae, Caesalpinioideae) tested against human colon and human glioblastoma cell lines [34]. Interestingly, the increase of neophytadiene concentration in fraction DA-FH (15.3 %) compared to DA-FF (3.9 %) led to higher cytotoxic effects in Vero cells.…”
Section: Resultsmentioning
confidence: 99%